Injection of CO2-saturated brine in geological reservoir: A way to enhanced storage safety. (November 2016) - Ahmad, Nawaz; Wörman, Anders; Sanchez-Vila, Xavier; Jarsjö, Jerker; Bottacin-Busolin, Andrea; Hellevang, Helge
Highlights: Injection of CO2 -saturated brine in a geological reservoir is modelled. Intense dissolution of carbonate minerals is observed. Significant ionic trapping of CO2 is observed. Injection of CO2 -saturated reduces leakage risk of free CO2 . Abstract: Injection of free-phase supercritical CO2 into deep geological reservoirs is associated with risk of considerable return flows towards the land surface due to the buoyancy of CO2, which is lighter than the resident brine in the reservoir. Such upward movements can be avoided if CO2 is injected in the dissolved phase (CO2aq ). In this work, injection of CO2 -saturated brine in a subsurface carbonate reservoir was modelled. Physical and geochemical interactions of injected low-pH CO2 -saturated brine with the carbonate minerals (calcite, dolomite and siderite) were investigated in the reactive transport modelling. CO2 -saturated brine, being low in pH, showed high reactivity with the reservoir minerals, resulting in a significant mineral dissolution and CO2 conversion in reactions. Over the injection period of 10 yr, up to 16% of the injected CO2 was found consumed in geochemical reactions. Sorption included in the transport analysis resulted in additional quantities of CO2 mass stored. However, for the considered carbonate minerals, the consumption of injected CO2aq was found mainly in the form of ionic trapping.